2021
DOI: 10.1089/crispr.2021.0018
|View full text |Cite
|
Sign up to set email alerts
|

Programming Cells by Multicopy Chromosomal Integration Using CRISPR-Associated Transposases

Abstract: Directed evolution and targeted genome editing have been deployed to create genetic variants with usefully altered phenotypes. However, these methods are limited to high-throughput screening methods or serial manipulation of single genes. In this study, we implemented multicopy chromosomal integration using CRISPRassociated transposases (MUCICAT) to simultaneously target up to 11 sites on the Escherichia coli chromosome for multiplex gene interruption and/or insertion, generating combinatorial genomic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…We also further investigated the importance of a palindromic sequence found 97–107 bp from the transposon right end boundary. Previous work suggested that this sequence might affect integration orientation, possibly by promoting transcription of the tnsABC operon, which would be consistent with empirical expression data and the AT-richness of the transposon end (48). To test this possibility, we mutated the palindromic sequence and found that variants with this sequence shifted the orientation preference towards T-LR, with just one arm of the palindrome (P B ) being sufficient to shift the orientation bias (Figure S4D-E).…”
Section: Resultssupporting
confidence: 82%
“…We also further investigated the importance of a palindromic sequence found 97–107 bp from the transposon right end boundary. Previous work suggested that this sequence might affect integration orientation, possibly by promoting transcription of the tnsABC operon, which would be consistent with empirical expression data and the AT-richness of the transposon end (48). To test this possibility, we mutated the palindromic sequence and found that variants with this sequence shifted the orientation preference towards T-LR, with just one arm of the palindrome (P B ) being sufficient to shift the orientation bias (Figure S4D-E).…”
Section: Resultssupporting
confidence: 82%
“…To enhance plasmid‐free heme synthesis, the fragment of pT7‐ hemH ‐pT7‐ ADB1‐hemB‐ADB3‐hemD‐ADB2‐hemC were multicopy chromosomal integrated using the CRISPR‐associated transposases (MUCICAT). [ 63,64 ] At first, plasmids pRE57I‐ADB‐hemBDC‐hemH, pTnsABC, and pQCascade were co‐transformed into E. coli C41(DE3) by electro‐transformation, and the transformants were obtained by incubation on triple antibiotic LB‐agar plate (50 µg mL −1 kanamycin, 100 µg mL −1 ampicillin, and 100 µg mL −1 streptomycin) for 16 h at 37 °C. In the following, the transformants were induced by incubation on the triple antibiotic LB‐agar plate containing different concentrations of anhydrotetracycline (100 ng mL −1 and 1000 ng mL −1 ) for 16 h at 37 °C, [ 64 ] and the copy numbers of pT7‐ hemH ‐pT7‐ ADB1‐hemB‐ADB3‐hemD‐ADB2‐hemC in obtained colonies were verified by colony PCR.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance plasmid-free heme synthesis, the fragment of pT7-hemH-pT7-ADB1-hemB-ADB3-hemD-ADB2-hemC were multicopy chromosomal integrated using the CRISPR-associated transposases (MUCICAT). [63,64] At first, plasmids pRE57I-ADB-hemBDC-hemH, pTnsABC, and pQCascade were co-transformed into E. coli C41(DE3) by electro-transformation, and the transformants were obtained by incubation on triple antibiotic LB-agar plate (50 μg mL −1 kanamycin, 100 μg mL −1 ampicillin, and 100 μg mL −1 streptomycin) for 16 h at 37 °C. In the following, the transformants were induced by incubation on the triple antibiotic LB-agar plate containing different concentrations of anhydrotetracycline (100 ng mL −1 and 1000 ng mL −1 ) for 16 h at 37 °C, [64] and the copy numbers of pT7-hemH-pT7-ADB1-hemB-ADB3-hemD-ADB2-hemC in obtained colonies were verified by colony PCR.…”
Section: Genetic Manipulation For the Construction Of Strains And Pla...mentioning
confidence: 99%
“…The hemA gene was deleted using the one-step gene inactivation method 53 . The CRISPR-Cas9 system 54 and the CRISPR-associated transposases (MUCICAT) 55 were used to overexpress endogenous heme biosynthetic genes. The plasmids pTetQCas-8 + IS186 (MC_0101250), pRE57I-GNAc (MC_0101251), pTnsABC (MC_0101189), and pCutamp (MC_0101104) were obtained from Molecular Cloud.…”
Section: Methodsmentioning
confidence: 99%